ANALISIS PERBANDINGAN KINERJA KEUANGAN BANK UMUM SYARIAH BUMD DENGAN MENGGUNAKAN METODE EAGLES - Nurfadjri Hidayanti; Arief Widyananto (MASLAHAH (Jurnal Hukum Islam dan Perbankan Syariah), 2022)
The background of this research is to analyze the financial performance of BUMD Islamic Banks. The problem formulation is as follows: How is the financial performance of PT? Bank Aceh Syariah and PT. Bank BJB Syariah using the EAGLES method in the 2016-2020 period; What is the comparison of the financial performance between Bank Aceh Syariah and Bank BJB Syariah in the 2016-2020 period? The purpose of this study is: to interpret the financial performance of PT. Bank Aceh Syariah and PT. Bank BJB Syariah during the 2016-2020 period and analyze the comparison of the financial performance of each bank. This research is a comparative quantitative study using secondary data that measures financial performance comparisons using the EAGLES method (Earning Ability, Asset Quality, Growth, Liquidity, Equity, Strategic Management) and using a comparative test, namely the Independent Sample t-Test. The data is listed in the Annual Report of Bank Aceh Syariah and Bank BJB Syariah. The study results show that the financial performance of Bank Aceh Syariah and Bank BJB Syariah has significant differences in the ratios of ROA, ROE, NPF, DGR, FGR, FDR, CAR, and SRQ. Based on the EAGLES method, Bank Aceh Syariah obtained a much better title than Bank BJB Syariah. Good in managing its financial aspects. This is reflected in the better financial ratios of Bank Aceh Syariah compared to Bank BJB Syariah.